2011
DOI: 10.1371/journal.pone.0020825
|View full text |Cite
|
Sign up to set email alerts
|

Microfabricated Physical Spatial Gradients for Investigating Cell Migration and Invasion Dynamics

Abstract: We devise a novel assay that introduces micro-architectures into highly confining microchannels to probe the decision making processes of migrating cells. The conditions are meant to mimic the tight spaces in the physiological environment that cancer cells encounter during metastasis within the matrix dense stroma and during intravasation and extravasation through the vascular wall. In this study we use the assay to investigate the relative probabilities of a cell 1) permeating and 2) repolarizing (turning aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 48 publications
2
84
0
Order By: Relevance
“…In 1977, Fidler and Kripke (9) put forward the concept of heterogeneity as the basis of tumor migration. From then on, it was realized that primary malignant tumor cells exhibit heterogeneity (10). Within a tumor, the biological characteristics and metastatic behaviors of various subgroups are not identical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1977, Fidler and Kripke (9) put forward the concept of heterogeneity as the basis of tumor migration. From then on, it was realized that primary malignant tumor cells exhibit heterogeneity (10). Within a tumor, the biological characteristics and metastatic behaviors of various subgroups are not identical.…”
Section: Discussionmentioning
confidence: 99%
“…FAK is a widely-expressed, non-receptor protein tyrosine kinase located in the cytoplasm. Phosphorylation of FAK mediates signaling events, is widely involved in various biological processes within cells, and contributes to tumor progression, including invasion, metastasis and angiogenesis (8)(9)(10)(11). FAK is closely associated with the migration of malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of such devices include the use of smaller amounts of reagents, time-lapsed observation of cell migration and quantitative assessment of cell migration. Mak et al [58] demonstrated that a physical gradient with increasing mechano-stress device produced a difference in the migratory behaviors of breast cancer cells, because of the tapered channels.…”
Section: Discussionmentioning
confidence: 99%
“…The result is shown in Figure 6. The outcomes provided by Mak et al [58] indicated that physical gradients led to distinctive migration patterns among normal and malignant cells. However, our results indicated that chemical gradients generated by EGF in the channels led to the migration of the normal, as well as malignant cells into the tapered channels.…”
Section: Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation